Title XIV. Of Aleatory Contracts (Art. 2982-2984) Book III, art. 2983, (La. 1940) (enacted 1808) - (:unkn) unknown (My University, 1808)
The law grants no action for the payment of what has been won at gaming or by a bet, except for games tending to promote skill in the use of arms, such as the exercise of the gun, foot, horse and chariot racing."
Keywords: SHOOTING RANGES OR GALLERIES